Evaluating a Digital Mindful Self-Compassion Intervention to Reduce Compassion Fatigue in Violence Service Workers: A Pilot Randomised Controlled Trial - Asriati, Rifka; Oriza, Imelda Ika Dian (Universitas Negeri Padang, 2025)
Compassion Fatigue (CF) often occurs among violence service workers, who face victims of violence daily, making them vulnerable to emotional exhaustion, decreased empathy, and burnout. This phenomenon not only affects their personal quality of life but also has the potential to reduce the quality of service they provide. This study aims to evaluate the effectiveness of a digital intervention using the Mindful Self-Compassion (MSC) approach in reducing compassion fatigue among violence case service workers. The research design is a randomized controlled pilot study with a total of 25 participants randomly divided into two groups: intervention (n=12) and wait-list control (n=13). The intervention was conducted over six sessions across six weeks, combining Zoom sessions, self-paced materials accessed via a website, and a WhatsApp group. CF was measured using the Professional Quality of Life Scale (ProQol-V), mindfulness using the Mindful Attention Awareness Scale (MAAS), and self-compassion using the Self-Compassion Scale (SCS), which has been adapted into Indonesian. The study results showed that the MSC intervention significantly reduced CF in the intervention group compared to the control group. Specifically, CF scores in the intervention group decreased from a pre-test mean of 57.17 to a post-test mean of 48.17, t(11) = 3.270, p = .007, indicating a statistically significant improvement. Meanwhile, the control group did not experience a significant change (p = .662). Between-group analysis at post-test confirmed a significant difference favoring the intervention group, t = -2.573, p = .017. In addition to the reduction in CF, mindfulness scores significantly increased in the intervention group from 56.67 to 61.92 (p = .009), and the common humanity subscale of self-compassion showed a notable improvement (p = .031). These results suggest that the digital MSC program effectively enhanced emotional resilience and mitigated compassion fatigue symptoms among trauma-exposed service providers. Qualitative feedback from participants indicated significant benefits from social support during the sessions and the accessibility of materials through the website. MSC intervention is effective in improving the psychological well-being of violence case service workers, thus the widespread implementation of the MSC program in this work environment is highly recommended to enhance mental health and service quality.